A formal design in the generation of an array PIN using a Petri net model and implementation for secure transactions. (9th November 2021) - Vaithyasubramanian, S.; Lalitha, D.; Christy, A.
Online banking and ATM transactions are being used by many people for they are easy to process and also very fast. Being highly customer-oriented, the two keys to any transaction is the user's identity and the PIN. Increasing threats and frauds are a major concern in the security of banking transaction. Though several measures are being taken, yet there is a necessity for a mathematical and contemporary model for transaction security. A novel PIN validation technique for online and ATM operation based on array password has been proposed in this paper. For the formal design and generation of array password Petri net, the 'mathematical modelling language' has been utilised. Due to its feasibility and clarity, this scheme can be used to improve the security flaws in e-banking and e-commerce. The implementation process, advantage and usability of the proposed method are presented in this paper.